PROFIL LIPID DAN MORTALITAS PASIEN INFARK MIOKARD AKUT DI RSUD PANEMBAHAN SENOPATI TAHUN 2015 - Darussalam, Miftafu; Nofiyanto, Muhamat (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Lipid profile is important as supporting data for patients with heart problem as it  is a state of fat seen in the levels of total cholesterol, LDL, HDL, and triglycerides. Disorders of lipid metabolism characterized by an increase or decrease in blood plasma is called dyslipidemia. Dyslipidemia has a close relationship with the occurrence of atherosclerosis and Acute Myocardial Infarction (AMI) as one of the leading causes of death. Objective: To determine  the relationship between lipid profile with the incidence of mortality in patients with acute myocardial infarction of Panembahan Senopati Bantul Hopsital in 2015. Methods: This study used a descriptive exploratory design with data retrieved from Panembahan Senopati Bantul District Hospital 2015 medical record with a total of 106 respondents. To analyze the data, the researchers used the Lamda test. Results: There are associations between mortality and: total cholesterol (p=.006) with strong level of closeness (.647); LDL (p= .009) with strong the level of closeness (.647); HDL (p= .017) with strong enough level of closeness(.529); and triglycerides (p= .003) with strong  level of closeness (.765). Conclusion: Mortality of AMI was statistically significant associated with total cholesterol, HDL, LDL, and triglycerides. Keywords: Acute Myocardial Infarction (AMI), lipid profile, mortality of AMI